Miniature Neurotransmission Regulates Drosophila Synaptic Structural Maturation - Choi, Ben Jiwon (Cell Press, 2014)
Miniature neurotransmission is the transsynaptic process where single synaptic vesicles spontaneously released from presynaptic neurons induce miniature postsynaptic potentials. Since their discovery over 60 years ago, miniature events have been found at every chemical synapse studied. However, the in vivo necessity for these small-amplitude events has remained enigmatic. Here, we show that miniature neurotransmission is required for the normal structural maturation of Drosophila glutamatergic synapses in a developmental role that is not shared by evoked neurotransmission. Conversely, we find that increasing miniature events is sufficient to induce synaptic terminal growth. We show that miniature neurotransmission acts locally at terminals to regulate synapse maturation via a Trio guanine nucleotide exchange factor (GEF) and Rac1 GTPase molecular signaling pathway. Our results establish that miniature neurotransmission, a universal but often-overlooked feature of synapses, has unique and essential functions in vivo.